MEDICATION BELIEFS DAN KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS TIPE II DENGAN BPJS - Yulia Prabhawaty; Santi Herlina (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
Type II Diabetes Mellitus (DMT-2) is a global disease characterized by blood glucose instability. With 537 million cases as of 2023 and a prevalence that continues to rise each year, DMT-2 has become the ninth leading cause of non-communicable disease-related deaths worldwide. The success of DMT-2 treatment is seen through the adherence to medication by those affected. One of the factors influencing medication adherence in DMT-2 patients is predisposition, such as medication beliefs and cost-related factors. In Indonesia, a solution to these cost-related concerns is provided through the Social Security Organizing Body (BPJS) as a form of health insurance. Medication beliefs are a critical factor in the management of medication adherence in DMT-2  patients to prevent complications and reduce mortality rates resulting from DMT-2. This research aims to determine the relationship between medication beliefs and medication adherence in DMT-2  patients covered by BPJS in the Jatinegara Sub-district Primary Health Care Centers (Puskesmas) area. The study is quantitative in nature with a cross-sectional approach conducted on 134 respondents using the Belief about Medicines Questionnaire (BMQ) and the Morisky Medication Adherence Scale-8 (MMAS-8) as measurement tools.The research results show that 61.2% of respondents have negative medication beliefs, while 38.8% have positive medication beliefs. Among the respondents, 78.4% exhibit low medication adherence, 17.2% have moderate adherence, and 4.5% have high adherence levels. The analysis using the Spearman Correlation Test indicates a significant relationship between the two variables (p<0.05), with a positive direction and a moderate degree of correlation (r=0.409). The conclusion drawn from this research is that as individuals have more positive medication beliefs, their medication adherence levels also increase.